KUALITAS PELAYANAN REKOMENDASI PENELITIAN BAGI MAHASISWA STRATA SATU (S-1) DI BADAN PELAYANAN PERIZINAN TERPADU (BP2T) PROVINSI RIAU - Aria Aldana; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Services provided by the Integrated Licensing Service Agency Riau Province to the applicant on the research must be in accordance with the general principles of public service so as to provide a quality service. Recommendations Research Services Licensing Service Agency Riau Province can be said of quality for Integrated Licensing Service Agency Riau Province has been providing services in accordance with the principle of service so as to get various public service achievements. The facilities provided by the Integrated Licensing Service Agency Riau Province adequate and have employees who have the ability to use the facilities available. Employees respond to any request for the public and can provide certainty of time in completing the application for the community. Then employees are always friendly and courteous in serving the community. The purpose of this study was to analyze the quality of services in the research recommendations Licensing Service Agency Riau Province and determine the factors that influence it. The results of this study indicate that the Integrated Licensing Service Agency Riau Province has a good quality service in serving the community and in accordance with the expectations and needs of the community. Starting from owned facilities are complete, the precision in serving the community, provide guarantees ketepan time in completing the work, expertise in using facilities owned, non-discriminatory, have a good response to the people who need help and serve the people in a friendly manner. Factors - factors that affect the quality of services in the research recommendations Licensing Service Agency Riau Province is infrastructure, human resources and leadership.Keywords: Quality of Service, Recommendation Research, Licensing Service Agency Riau Province